Vehicle Security System Using Zigbee Technology - Syed Mokhtar, Syed Abdul Wafiy Aiman; Hashim, Nik Mohd Zarifie; Mohamad, Najmiah Radiah; Jaafar, Anuar; Salleh, Azahari (International Journal for Advance Research in Engineering and Technology, 2014)
-